2010
DOI: 10.1890/09-0422.1
|View full text |Cite
|
Sign up to set email alerts
|

Constructing confidence: rational skepticism and systematic enquiry in local ecological knowledge research

Abstract: Key attributes of the social research contributions on indigenous ecological knowledge (IEK), local ecological knowledge (LEK), and traditional ecological knowledge (TEK) are analyzed using the most frequently cited literature generated by the "ISI Web of Knowledge" and "Google Scholar" search engines. They are further exemplified by an examination of two contrasting approaches to the analysis of IEK/LEK/TEK. The results show that IEK/LEK/TEK is treated predominantly via definitions, and few articles examine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 46 publications
2
127
1
3
Order By: Relevance
“…Scientists call for greater efforts in the definition and validation of the integrity of IEK knowledge claims, and some Indigenous groups have also sought validation of their IEK knowledge claims by science (Evans et al 2009, Gratani et al 2011. Other Indigenous people resist scientific efforts to integrate with IEK as a result of concerns that power relations embedded in IEK projects will further marginalize their interests (Smith 1999, Agrawal 2002, Davis and Ruddle 2010. Nevertheless, connections between ownership of IEK and ownership of land and sea in Australian Indigenous cultures trigger significant responsibilities for maintaining control (Rose 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists call for greater efforts in the definition and validation of the integrity of IEK knowledge claims, and some Indigenous groups have also sought validation of their IEK knowledge claims by science (Evans et al 2009, Gratani et al 2011. Other Indigenous people resist scientific efforts to integrate with IEK as a result of concerns that power relations embedded in IEK projects will further marginalize their interests (Smith 1999, Agrawal 2002, Davis and Ruddle 2010. Nevertheless, connections between ownership of IEK and ownership of land and sea in Australian Indigenous cultures trigger significant responsibilities for maintaining control (Rose 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding approaches to knowledge integration in these diverse Australian examples may help build global understanding of the processes of IEK and western science integration to manage for sustainability. However, http://www.ecologyandsociety.org/vol17/iss1/art23/ integration is affected by diverse factors including approaches to inquiry into IEK, adaptive co-management context, and the intrinsic qualities of the natural resource (Agrawal 2002, Davies 2003, Telfer and Garde 2006, Davies and Holcombe 2009, Wohling 2009, Davis and Ruddle 2010. Governance forms, including power relationships, multi-scalar polycentric connections, orchestration of networks, and negotiation of diverse Indigenous and state institutions, shape interactions that block, bridge or enable integration of IEK and western science (Olsson et al 2004, Folke et al 2005, Olsson et al 2006, Ostrom 2007.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main results that have emerged from our study is the uneven distribution of LEK among the communities studied, and thus, all individuals in a culturally homogeneous community cannot be assumed to reflect the same level of knowledge (Davis and Wagner 2003;Davis and Ruddle 2010). We found that the maintenance of LEK depended on individual and collective factors such as the time spent in the area (TIME), the parents' dedication to agriculture (PARENTS), the transmission of knowledge Significance: * B10 %, ** B5 %; *** B1 %.…”
Section: Demographic and Technological Driving Forces Affecting The Mmentioning
confidence: 98%
“…The demographic driver of change has a huge effect on the de-structuring of the social community and the embedded knowledge system for two main reasons: (1) the lack of contact with the local management practices and (2) the rupture of the transmission system. Both aspects interfere with two key attributes of LEK: (1) its development through direct experience and (2) its transmission between or among generations (Davis and Ruddle 2010). When the intra-and intergenerational web of relationships breaks down, younger people have difficulty making sense of their observations in the environment (Davidson-Hunt and Berkes 2003).…”
Section: Demographic and Technological Driving Forces Affecting The Mmentioning
confidence: 99%
“…Incluye no solamente conocimientos prácticos, sino también creencias y significaciones construidas a lo largo del tiempo mediante la interrelación e interacción entre una comunidad humana y el ecosistema del cual es parte. Involucra un conjunto de saberes que surge de la continuidad histórica entre un grupo humano y su lugar en el planeta, un atributo social a menudo transmitido por mecanismos que no son de índole escrita, incluyendo tradiciones orales, mitos y leyendas, rituales, manifestaciones de artes plásticas y corporales, entre otros (Davis y Ruddle 2010).…”
Section: Conocimiento Ecológico Local Y Biología De Conservaciónunclassified